Brazilian agriculture in the 1990s: Impact of the policy reforms - Steven M. Helfand; Gervásio Castro de Rezende (Institute for Applied Economic Research (ipea), 2015)
This paper describes the changes in economic policies and in macroeconomic conditions in the 1990s and analyses their impact on the agricultural sector in Brazil. We emphasize four aspects of the reform period that were either unexpected or not given sufficient attention by authors writing in the period prior to the reforms. The first issue relates to the importance that events outside of the agricultural sector, specially the stabilization problems, have not only for the performance of the sector but also for the timing and sequence of policy reform. A second issue that we emphasize is that policy reform involved far more than trade liberalization. Deregulation and the reform of rural credit and support price policy have been central as well. A third issue that was not given sufficient attention by the pre-reform analyses that focused on agricultural prices is the impact of policy reform on input markets and productivity. We identify changes in input markets as one of the key components of the adjustment process. A fourth and final issue that we address is that policy reform had a highly differentiated impact on the sector. Reform was neither uniformly beneficial, nor entirely prejudicial. Thus, our analysis seeks to distinguish between different groups of products, such as importables and exportables, geographic regions, farm sizes, and sub-periods. The paper emphasizes also that, since not all reforms were introduced simultaneously, the 1990s should be treated as a decade of transition in which the old model was replaced, but not all of the features of the new model were firmly established.
Keywords: 330